Association between NPC1L1 and HMGCR gene polymorphisms with residual cholesterol risk in patients with premature triple-vessel disease. (14th October 2021) - Li, J; Zhao, X; Yang, Y; Gao, R; Yuan, J; ,
Abstract: Background: Management of dyslipidemia is the primary recommend in current guidelines in patients with coronary heart disease (CHD). Despite intense statins therapy, patients with low-density lipoprotein cholesterol (LDL-C) level of more than 1.8 mmol/L still have residual cholesterol risk. Premature triple-vessel disease (PTVD) is a severe CHD. Recent studies have established that both residual cholesterol risks and PTVD were associated with adverse cardiovascular events. Niemann-Pick C1-like 1 (NPC1L1) and 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) is involved in exogenous cholesterol absorption and endogenous cholesterol synthesis respectively, which play a vital part on dyslipidemia. Purpose: The present study aimed to investigate the association between NPC1L1 and HMGCR gene polymorphisms and residual cholesterol risk in patients with PTVD. Methods: A total of 609 PTVD patients treated with statins were consecutively enrolled from April 2004 to February 2011. Residual cholesterol risk was defined as low-density lipoprotein cholesterol (LDL-C) >1.8 mmol/L. According to LDL-C levels, the patients were divided into two groups: residual cholesterol risk group (n=521, >1.8 mmol/L) and non-residual cholesterol risk group (n=88, LDL-C ≤1.8 mmol/L). Four single nucleotide polymorphisms (SNP) of NPC1L1 gene including rs11763759, rs4720470, rs2072183 and rs2073547 and three SNPs of HMGCR gene including rs12916, rs2303151 and rs4629571 were genotyped. Results: After adjusted for age and sex, multivariate logistic regression analysis showed that rs12916 of HMGCR gene was associated with 2.082 times higher residual cholesterol risk in recessive model (OR: 2.082, 95% CI: 1.156–3.749, P=0.015), and the homozygous TT of rs12916 (OR: 2.262, 95% CI: 1.155–4.429, P=0.017) was associated with 2.262 times higher residual cholesterol risk in codominant model while there was no significant association for the heterozygous CT of rs12916 in codominant model (OR: 1.140, 95% CI: 0.678–1.917, P=0.621). There was no significant association between the SNPs of NPC1L1 gene and residual cholesterol risk in various models (P>0.05). Conclusions: We reported for the first time that the rs12916 on HMGCR gene were associated with residual cholesterol risk in patients with PTVD, providing new insight in genetic treatment in dyslipidemia. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): CAMS Innovation Fund for Medical Sciences (CIFMS); Key Science and Technology Project of Shihezi